Over my dead body - Archer, Jeffrey, 1940- (Archer, Jeffrey, 1940- William Warwick novels., 2021)
At the heart of three murder investigations--one in London involving a cold case, one in Geneva involving a millionaire art collector and one in New York involving a wealthy dynasty, Detective Chief Inspector William Warwick must catch the killers before it's too late.